FOTOGRAFI PERJALANAN DENGAN OBJEK KEPULAUAN KARIMUNJAWA - Sigit Hardiyanto (Saraswati)
Photography is believed to tell the return of the reality that is seen by the eye, in the making of the final project work of The TripPhotography to Karimunjawa Island, using the basis of the theory of the creation of documentary photography by applying photographic documentary into a sightseeing trip to the Karimunjawa Island, covering back in a series of stories which will be described to the public as information to others about the tour on the Karimunjawa Island. A trip can be conducted by many people in different ways, even if it is in the same destination. Therefore, every pictures that is produced by photographers that are documenting a journey to places among the tourist will always differrent.   Karimunjawa archipelago consists of 27 islands; Karimunjawa, Kemujan, Parang, Nyamuk (mosquitos), Genting, Menjangan Besar, Menjangan Kecil, Cemara Besar, Cemara Kecil, Gleang, Burung, Bengkoang, Menyawakan, Kembar, Katang, Krakal Besar, Krakal Kecil, Sintok, Mrico / Mrican, Tengah, Pinggir, Kecil, Gundul, Seruni, Sambangan, Cendikian and Kumbang. With the main island at the center of his district, and is located in Jepara district with 98 kms distance the trip uses boats. Karimunjawa has the natural-beauty worthy of a tour destination. This project is made from the process of observating, explorating, tol the formating process works with digital printed on glossy photo paper and packed in a frame for display.   This photography project is a hobby that is applied to the final project, then to be told again about the trip conducted by the author in Karimunjawa with the medium of documentary photography that is applied into the tour as information to the public about the realities of travel in Karimunjawa and also for personal archiving on Karimunjawa.   Keywords: Photography, Travel, Publications